(untitled) (Journal of Surgical Sciences, 2026)
Background: The arteria dorsalis pedis (ADP) flap has been widely described in reconstruction of soft tissue loss over dorsum of hand. However, some details require refinement to improve functional results. Methods: From August 2018 to July 2020, 20 patients (13 males and 7 females), mean age 29 years (range, 18-48 years) with soft tissue loss over dorsum of hand were treated with ADP Free Flap. Fasciocutaneous flaps were used for patients with only soft tissue defects. All flaps were sensate. After reconstruction of the defects, functional outcomes were evaluated with the Quick DASH scale. Results: One flap was lost. 19 (95%) flaps survived. Average flap thickness of 4.9 mm underwent innervation by an end-to-end neurorrhaphy. On basis of methodology parameters, flap reconstruction was exhibited 65% excellent, 30% good and 05% poor. QuickDASH scale was used for motor function evaluations and the average percentage of disability was found 19.73%. Average 09 months follow up, perception of pain and touch was present in all patients. Temperature in 84.22% patients on the entire flap and two-point discrimination was showed 16.42±5.04 mm in the proximal half and 18.52±4.35 mm in the distal half of flap. No patient experienced difficulty walking. Conclusions: Simultaneous thinning and innervation of the ADP flap led to a good functional outcome with a low percentage of disability, which could result in minor surgical procedures and better recovery of motor and sensory function. Journal of Surgical Sciences 2022;26(2): 60-67